GAMBARAN PENGETAHUAN DAN SIKAP IBU DENGAN PENCEGAHAN PERIODONTITIS PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS TODDOPULI - Manggarsari, Yayie; Nadiah, Nadiah; Ancis, Nur; Pariati, Pariati; Feblina, Ayu Rahayu (Jurnal Ilmiah Amanah Akademika, 2022)
Based on an initial survey conducted by interviewing 8 pregnant women on January 21 2022 at the Antang Perumnas Health Center with interviews, 6 out of 8 pregnant women stated that they did not know about periodontitis. And 2 out of 8 pregnant women know about periodontitis and how to prevent periodontitis. This research uses a descriptive analytical method, namely to determine the description of mothers' knowledge and attitudes regarding the prevention of periodontitis in pregnant women in the Antang Perumnas Health Center Work Area in 2022. From the results of the research, a description of the respondents' knowledge was obtained, namely 64 respondents who had less knowledge (71.1% ), respondents who had good knowledge were 26 people (28.9%). The description of respondents' attitudes is that 49 (54.4%) respondents had a poor attitude towards preventing periodontitis, 41 (45.6%) respondents had a good attitude towards preventing periodontitis. It is hoped that this research can reduce maternal morbidity rates at the city level and become input for the Health Service to carry out activities to prevent dental and oral diseases in pregnant women.